2008
DOI: 10.1097/nen.0b013e31816ff780
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Repair

Abstract: DNA damage is a form of cell stress and injury that has been implicated in the pathogenesis of many neurologic disorders, including amyotrophic lateral sclerosis, Alzheimer disease, Down syndrome, Parkinson disease, cerebral ischemia, and head trauma. However, most data reveal only associations, and the role for DNA damage in direct mechanisms of neurodegeneration is vague with respect to being a definitive upstream cause of neuron cell death, rather than a consequence of the degeneration. Although neurons see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(84 citation statements)
references
References 95 publications
(148 reference statements)
1
82
0
1
Order By: Relevance
“…8-OHdG is a product of highly mutagenic DNA oxidative damage; moreover, it is widely expressed in the nucleus, mitochondria, and metabolites in eukaryotic cells, and prokaryotic cells. Therefore, it can be used as a marker for the detection of DNA damage (Martin, 2008). In this study, we observed an increase in 8-OHdG expression in hepatocytes treated with increasing levels of UA for greater periods, indicating that UA enhances DNA damage in hepatocytes.…”
Section: Discussionsupporting
confidence: 49%
“…8-OHdG is a product of highly mutagenic DNA oxidative damage; moreover, it is widely expressed in the nucleus, mitochondria, and metabolites in eukaryotic cells, and prokaryotic cells. Therefore, it can be used as a marker for the detection of DNA damage (Martin, 2008). In this study, we observed an increase in 8-OHdG expression in hepatocytes treated with increasing levels of UA for greater periods, indicating that UA enhances DNA damage in hepatocytes.…”
Section: Discussionsupporting
confidence: 49%
“…When the rate of DNA damage by ethanol exceeds the capacity of the cell to repair it, the accumulation of errors may result in early senescence, apoptosis, or cancer. ROS has been pointed out as one of the main causes of single-strand DNA damage (Martin 2008). In this study, there was a positive moderate to strong correlation between ROS levels and single-strand DNA damage in the striatum, cerebellum, hypothalamus, and pre-frontal cortex.…”
Section: Discussionmentioning
confidence: 73%
“…Neurotoxins have been shown to cause an increase in systemic DNA damage. Physiological and oxidative stresses relate to the pathogenic development of neurodegenerative and psychiatric diseases (Forlenza & Miller 2006, Martin 2008, Rybka et al 2013). Progressive neuronal DNA damage in aging brains are closely linked with the onset of neurodegenerative disorders (Lindahl 1993).…”
Section: Introductionmentioning
confidence: 99%